Influence of Bypass Diode Thermal Design on Photovoltaic Modules - Irawati, Irawati; Nurtiyanto, Woro Agus; Putra, Rizji Yanto Dwi (Universitas Pamulang, Prodi teknik Elektro, 2024)
The absorption rate of the photovoltaic module is the ratio of the total radiation absorbed by the photovoltaic module to the total radiation that hits the surface of the photovoltaic module. Solar cells convert the sun's optical energy directly into electrical energy, the main problem associated with solar cells is their lower efficiency. This change in the temperature of the photovoltaic cells is caused by the temperature of the cloud conditions and the wind speed in the environment around the placement of the photovoltaic modules. Some of the test parameters and explains the impact and test results, the function of the bypass diode used in the photovoltaic module in optimizing the absorption of sunlight which aims to find out how to use the appropriate bypass diode and how to find out the suitability of the bypass diode thermal value in the photovoltaic module. The bypass diode suitable for the use of photovoltaic modules can be determined by looking at the suitability of the thermal test on each type of bypass diode. Based on the temperature values ​​measured in the bypass diode thermal test by firing the short circuit current listed on the photovoltaic module marking, nothing exceeds the failure limit value, which is above 200°C listed on the test standard, for the highest junction temperature value is on the ISOLAR-1 brand namely 188.1°C while the lowest junction temperature value is at the Fastpec brand, 139.2°C.